COMPARATIVE ANALYSIS OF POST OPERATIVE ARRHYTHMIAS, AMONG PATIENTS UNDERGOING OFF-PUMP VERSUS ON-PUMP CORONARYARTERY BYPASS GRAFTING (The Research of Medical Science Review, 2025)
Background: This study addresses the need for a comprehensive evaluation of outcomes in coronary artery bypass grafting (CABG) procedures, specifically comparing the on- pump and off-pump techniques. Recognizing the evolving landscape of cardiac surgery, understanding the implications of these methods is crucial for optimizing patient care. Methodology: A retrospective analysis was conducted on a cohort of patients who underwent CABG, categorizing them based on whether on-pump or off-pump techniques were employed. Patient records were scrutinized for the occurrence of postoperative arrhythmias, length of hospital stay, and mortality rates. Statistical analyses were applied to discern significant differences between the two surgical approaches. Results: The study revealed notable variations in postoperative outcomes between on-pump and off-pump CABG. The incidence of arrhythmias, length of hospital stay, and mortality rates were distinct in each group. These findings shed light on the potential advantages and drawbacks associated with each method, informing future surgical decisions and patient management. Conclusion: In conclusion, our comparative analysis underscores the importance of tailoring CABG approaches to individual patient profiles. The study provides valuable insights into the nuanced outcomes of on-pump and off-pump techniques, facilitating evidence- based decision-making for cardiac surgeons and enhancing the overall quality of care for patients undergoing coronary artery bypass grafting